2021
DOI: 10.1186/s12889-021-12058-z
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of adverse childhood experiences and gender as risk factors for depression and anxiety disorders in US adults: a cross-sectional study

Abstract: Background Exposure to adverse childhood experiences (ACEs) and being female are distinct risk factors for having a major depressive episode (MDE) or an anxiety disorder (AD) in adulthood, but it is unclear whether these two risk factors are synergistic. The purpose of this study was to determine whether exposure to ACEs and being female are more than additive (synergistic) in their association with MDE and AD in US adults. Methods We pooled cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 69 publications
2
12
0
1
Order By: Relevance
“…The role of environmental factors in the pathogenesis of MDD has attracted greater attention from physicians and researchers ( Foster et al, 2017 ; O’Mahony et al, 2017 ). Several studies have shown that people who have experience of physical abuse (PA) or emotional abuse (EA) are more likely to suffer from depression ( Biedermann et al, 2021 ; Husain et al, 2021 ), and the severity of symptom is strongly associated with childhood maltreatment ( Whitaker et al, 2021 ; Yang et al, 2021 ; Rep et al, 2022 ). According to a study, the effects of childhood maltreatment could last for decades and are strongly associated with the onset of mental disorders at an older age ( Macpherson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of environmental factors in the pathogenesis of MDD has attracted greater attention from physicians and researchers ( Foster et al, 2017 ; O’Mahony et al, 2017 ). Several studies have shown that people who have experience of physical abuse (PA) or emotional abuse (EA) are more likely to suffer from depression ( Biedermann et al, 2021 ; Husain et al, 2021 ), and the severity of symptom is strongly associated with childhood maltreatment ( Whitaker et al, 2021 ; Yang et al, 2021 ; Rep et al, 2022 ). According to a study, the effects of childhood maltreatment could last for decades and are strongly associated with the onset of mental disorders at an older age ( Macpherson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It should also be considered that sample characteristics may have influenced the current findings. The majority of the sample were women, and prior research has widely documented that women are more likely to report exposure to traumatic events (Whitaker et al, 2021) and higher PTSS severity than men (Breslau et al, 1997). Future studies should be conducted to analyze these hypotheses in samples in samples with a higher proportion of men.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a subsequent meta-analysis has failed to find any sex differences in the association between CM and MDD morbidity or in the severity of depressive symptoms in adulthood [ 31 ]. In contrast, a recent study revealed a synergistic effect of female sex and unfavorable childhood experiences on the 12-month prevalence of major depressive episodes in US adults [ 32 ]. Similarly, a Brazilian population-based study identified CM as a significant risk factor for MDD in women rather than in men [ 33 ].…”
Section: Introductionmentioning
confidence: 99%